Measuring B1 distributions by B1 phase encoding. Issue 1 (17th January 2016) - Jordanova, Kalina V.; Nishimura, Dwight G.; Kerr, Adam B.
Abstract : Purpose: We propose a method to acquire B 1 distribution plots by encoding in B 1 instead of image space. Using this method, B 1 data is acquired in a different way from traditional spatial B 1 mapping, and allows for quick measurement of high dynamic range B 1 data. Methods: To encode in B 1, we acquire multiple projections of a slice, each along the same direction, but using a different phase sensitivity to B 1 . Using a convex optimization formulation, we reconstruct histograms of the B 1 distribution estimates of the slice. Results: We verify in vivo B 1 distribution measurements by comparing measured distributions to distributions calculated from reference spatial B 1 maps using the Earth Mover's Distance. Phantom measurements using a surface coil show that for increased spatial B 1 variations, measured B 1 distributions using the proposed method more accurately estimate the distribution than a low‐resolution spatial B 1 map, resulting in a 37% Earth Mover's Distance decrease while using fewer measurements. Conclusion: We propose and validate the performance of a method to acquire B 1 distribution information directly without acquiring a spatial B 1 map. The method may provide faster estimates of a B 1 field for applications that do not require spatial B 1 localization, such as the transmit gain calibration of the scanner, particularly for high dynamic B 1 ranges. Magn Reson Med 77:229–236, 2017. © 2016 Wiley Periodicals, Inc.